علامہ عبد الغنی نابلسی رحمۃ اللہ علیہ : احوال و آثار اور علمی خدمات : Allama Abdul Ghani Nabulsi: Life, Works, and Scholarly Contributions - Shaukat Ali; Dr. Humayun Abbas (AL-IDRAK JOURNAL, 2024)
In the annals of Islamic history, there have been a select few individuals who have delved into the intricate relationship between jurisprudence and Sufism. This area of research, despite its profound significance, has garnered minimal attention. Following in the footsteps of Abdul Wahab Sha'rani, Allama Abdul Ghani Nabulsi emerged as a luminary in the eleventh century Hijri, dedicating his scholarly pursuits to this crucial subject. He stands as a towering figure, equally adept in both jurisprudence and Sufism. Allama Abdul Ghani Nabulsi bequeathed a rich legacy of scholarly works encompassing both fiqh al-zahir (apparent jurisprudence) and fiqh al-batin (inner jurisprudence). His practical life mirrored his profound knowledge, earning him the esteemed reputation of a great jurist during his era while simultaneously being revered as a prominent Sufi leader. This essay aims to shed light on this remarkable intellectual and spiritual personality, delving into his perspectives and thought processes.